EVALUASI EFEKTIVITAS CORE TAX ADMINISTRATION SYSTEM DITINJAU DARI MODEL TASK-TECHNOLOGY FIT PADA KPP PRATAMA GIANYAR - Ni Komang Natasya Maharani; Gusi Putu Lestara Permana (Universitas Prof.Hazairin,SH Bengkulu, 2026)
This study aims to assess how Task Characteristics and Technology Characteristics affect Task and Technology Fit and its impact on Performance Impact on Core Tax Administration System users at KPP Pratama Gianyar. The background of the research emerged from the large number of taxpayers who still need assistance in operating the system, thus indicating a possible mismatch between the demands of the task and the capabilities of the technology used. The research approach used was quantitative with a purposive sampling technique on 100 respondents who had used the system at least once. Data analysis was carried out using Structural Equation Modelling (SEM) based on Partial Least Squares (PLS). The results of the study show that Task Characteristics and Technology Characteristics have a significant positive effect on Task and Technology Fit. In addition, Task and Technology Fit has also been proven to have a significant positive influence on Performance Impact. These findings emphasize that the compatibility between tasks and technology is an important aspect in improving the effectiveness of the use of the Core Tax Administration System as well as the performance of its users.